Implementasi Rescheduling Akad IMBT Berdasarkan Fatwa DSN-MUI No.134/DSN-MUI/II/2020 : Studi Kasus Unit Usaha Syariah PT Bank DKI - Mufidah Js.Dahlan; Muzayyanah (JURNAL ILMIAH NUSANTARA, 2026)
The purpose of this study is to analyze the implementation of DSN-MUI Fatwa No. 134/DSN-MUI/II/2020 concerning real costs in the rescheduling of the Ijārah Muntahiya bi at-Tamlik (IMBT) contract at the Sharia Business Unit of PT Bank DKI. This issue is significant because rescheduling financing has the potential to lead to usury (riba) practices due to additional costs, a matter that contradicts the principle of justice in sharia finance. This qualitative research uses an empirical case study approach. Primary data was collected through observation and interviews, while secondary data was obtained from literature. The research findings show two main results. First, the restructuring process begins with the customer's application, followed by a bank evaluation, and is concluded with a new contract. Second, the practice of charging real costs at the Sharia Business Unit of PT Bank DKI has been implemented in accordance with the DSN-MUI Fatwa, with costs limited to factual expenses, such as stamp duty. This con clusion proves that the bank has successfully implemented sharia principles in handling non-performing financing.